Genomic and functional insights into the diversification of the elongation factor eEF1Bγ in fungi. (December 2022) - Renou, Julien; Sormani, Rodnay; Gelhaye, Eric; Didierjean, Claude; Morel-Rouhier, Mélanie
Abstract: eEF1Bγs are proteins found in all eukaryotes and have a role in protein translation, being part of the nucleotide exchange factor eEF1B of the elongation factor complex 1. They are unique because of their organization as a fusion between a glutathione transferase (GST) domain and an elongation factor EF1G (PF00647) domain. The main described function of the GST domain in eEF1Bγ is to ensure the proper scaffolding of the different subunits in the eEF1B complex, by interacting with eEF1Bα subunit. Several evidences also suggest that this domain has a role in cellular redox control because it displays enzymatic activity using glutathione as co-substrate. This opens the question of a dual role of eEF1Bγ in cells both in protein translation and stress response, either in a concomitant or competitive way. By analyzing the diversity of eEF1Bγ sequences in fungi, we show that this class of proteins is subjected to diversification within these microorganisms. The challenge is now to understand the impact of such diversification in eEF1Bγ functions both related to protein translation and stress response, and whether this could have driven the ability of fungi to adapt to constraints. Graphical abstract: Image 1 Highlights: - The elongation factor eEF1Bγ is an active glutathione transferase. - Its function could be both linked to protein translation and redox regulation. - Sequence diversity exists among fungi. - A high number of eEF1Bγ sequences lack the C-term domain.